Global Economic Prospects, January 2019 : Darkening Skies - World Bank (Washington, DC: World Bank, 2018)
Global economic prospects have darkened. Financing conditions have tightened, industrial production has moderated, and trade tensions remain elevated. The recovery in emerging market and developing economies has stalled, and some countries have experienced significant financial stress. Downside risks have increased, including the possibility of disorderly financial market movements and escalating trade disputes. It is thus critical to rebuild policy buffers while fostering potential growth by boosting human capital, promoting trade integration, and addressing informality. In addition to discussing global and regional economic developments and prospects, this edition of Global Economic Prospects includes a chapter on the challenges posed by informality and associated policy options. The report also contains pieces on the remarkable decline in inflation in emerging market and developing economies over the past decades, rising debt vulnerabilities in low-income countries, and the implications of large spikes in food prices for poverty. Global Economic Prospects is a World Bank Group Flagship Report that examines global economic developments and prospects, with a special focus on emerging market and developing countries, on a semiannual basis (in January and June). The January edition includes in-depth analyses of topical policy challenges faced by these economies, while the June edition contains shorter analytical pieces.